2015
DOI: 10.1111/jfpp.12554
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Microbiological Properties of Tarhana Enriched with Immature Wheat Grain

Abstract: In this study, the effect of immature wheat grain (IWG) supplementation on the tarhana formulation was investigated by determining color values and some chemical and microbiological properties. Flours obtained from IWG, harvested at 26 (IWG-1) and 36 days (IWG-2) after anthesis, were used in the tarhana formulation as a replacement of white wheat flour in concentrations of 10, 30 and 50%. Ash, Ca, Mg, K, P and Zn contents of tarhana samples increased by IWG-1 addition. IWG-2 addition resulted in an increase in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…The protein content initially increases and then decreases at the last stage of wheat grains development. Similar results were found that the protein content of Immature Wheat Grain-2 (17.84 %, DAF-36) was found to be higher than that of Immature Wheat Grain-1 (13.53 %, DAF-26) in a study by Aktaş et al (2015) on the physical and chemical properties of immature wheat flours. The reduction in the protein content of the flours with three degrees after roasting attributed to the denaturation and associated with the involvement of amino acids in Maillard reactions during the thermal process ( Bekedam et al, 2008 ).…”
Section: Discussionsupporting
confidence: 83%
“…The protein content initially increases and then decreases at the last stage of wheat grains development. Similar results were found that the protein content of Immature Wheat Grain-2 (17.84 %, DAF-36) was found to be higher than that of Immature Wheat Grain-1 (13.53 %, DAF-26) in a study by Aktaş et al (2015) on the physical and chemical properties of immature wheat flours. The reduction in the protein content of the flours with three degrees after roasting attributed to the denaturation and associated with the involvement of amino acids in Maillard reactions during the thermal process ( Bekedam et al, 2008 ).…”
Section: Discussionsupporting
confidence: 83%
“…The aroma active compounds of tarhana are mainly aldehydes, ketones, phenols, esters, alcohols, terpenes, sulfur compounds, furans, and acids which are also very important for consumer taste (Gocmen et al., 2004; Temiz & Tarakçı, 2017). Tarhana is also a good source of Mg, P, Ca, Fe, Zn, and K (Aktas et al., 2015a; Bilgiçli et al., 2006; Daglioǧlu, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, researchers have investigated immature grains as food materials [9,10,11,12]. Immature wheat grain contains less starch and protein contents and more fiber, essential amino acids, and soluble sugars than mature wheat [10,13].…”
Section: Introductionmentioning
confidence: 99%